2023
DOI: 10.1212/wnl.0000000000206882
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Norepinephrine in Cerebellar Modulation and Stress-Induced Episodic Ataxia?

Abstract: The cerebellum receives noradrenergic input from the locus ceruleus (LC).1-3 The LC input to the cerebellar cortex is diffuse and targets mainly the molecular layer but also the Purkinje and granule cell layers.4,5 Norepinephrine (NE), acting through different adrenoceptor subtypes localized presynaptically and postsynaptically in the various components of the cerebellar circuit, has a complex modulatory effect on the tonic firing of Purkinje cells, which control the output of the cerebellum through the cerebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The mechanism, how blockade of α1-ARs prevents stress-induced attacks of motor dysfunction was recently postulated ( 73 , 74 ). Snell et al showed that NE binding to α1-ARs results in a reduced open probability of small conductance K + channels (SK) through phosphorylation of SK-associated calmodulin (CaM) through SK2-associated casein kinase 2 (CK2) ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism, how blockade of α1-ARs prevents stress-induced attacks of motor dysfunction was recently postulated ( 73 , 74 ). Snell et al showed that NE binding to α1-ARs results in a reduced open probability of small conductance K + channels (SK) through phosphorylation of SK-associated calmodulin (CaM) through SK2-associated casein kinase 2 (CK2) ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially prazosin was shown to cause headache, dizziness, palpitation and tachycardia ( 84 , 85 ). Development and further exploration of α1 D -AR specific drugs may not only be beneficial for EA2 patients, but for all patients suffering from episodic neurological disorders where stress is a common trigger ( 74 ). The α1 D -AR may provide a more specific therapeutic target in treating episodic neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The other main component of the BBB is the astrocyte [6], which plays an essential role in establishing and maintaining it. Astrocytic end-feet form a coating network around the brain vasculature, the glia limitans, and, together with endothelial cells and pericytes [7], they form the BBB, separating the bloodstream from the brain parenchyma. All components interact with each other, contributing to BBB function, development, and maintenance [4].…”
Section: Introductionmentioning
confidence: 99%